Impact of Relationship Status and Quality (Family Type) on the Mental Health of Mothers and Their Children: A 10-Year Longitudinal Study - Hannighofer, Jasmin; Foran, Heather; Hahlweg, Kurt; Zimmermann, Tanja (Frontiers in Psychiatry, 2017)
Mothers and children of single or unstable relationships have higher rates of mental health problems than those in stable two-parent-families. Despite results that mothers and children of conflictual two-parent-families also show impairments, most studies do not consider relationship quality. Therefore the present study combines relationship status and relationship quality to a “family type”. The present study compares German mothers and children of two-parent-families with high relationship quality to those from two-parent-families with a low quality, single mothers and unstable families. Data of n = 249 families from a ten-year-follow-up-longitudinal-study show that mothers with a high relationship quality show the highest levels of mental health whereas all other groups show at least a 3.2 times higher probability of mental health symptoms. Children of mothers in unstable relationships show a 8.2 times higher probability to emotional or behavioral problems than children of mothers with high relationship quality. Therefore, not only relationship status but also relationship quality should be combined and this “family type” should be considered in future research.